2017
DOI: 10.1080/19942060.2017.1322148
|View full text |Cite
|
Sign up to set email alerts
|

A discussion on the validity domain of the weighted residuals model including the Marangoni effect for a thin film flowing down a uniformly heated plate

Abstract: In this paper, the validity of the Weighted Residuals Model (WRM), including the Marangoni effect, is investigated through linear stability analyses and two-dimensional nonlinear numerical simulations. The linear stability analyses with the WRM show that the model's accuracy decreases nearly linearly with the Marangoni number for each Reynolds number and achieves a maximum at approximately Re = 4 for each Marangoni number. This is quite different from the isothermal case, for which the error increases monotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The inclination angle of the substrate is set to 90°(between the substrate and the horizon), and thus the inclination number is taken to be Ct = 0. On the Bi and Bi w values taken, Our previous paper (Liu et al, 2017), Kobov experiments (Kabov, Scheid, Sharina, & Legros, 2002), and Kallidasis et al (2012) have all shown that as Bi and Bi w are less than 1, their effects on the Marangoni effect for film flow instability is small. Due to poor heat transfer characteristics at the liquid-gas interface and solid-gas interface, the actual Bi and Bi w values are very small.…”
Section: Linear Stability Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The inclination angle of the substrate is set to 90°(between the substrate and the horizon), and thus the inclination number is taken to be Ct = 0. On the Bi and Bi w values taken, Our previous paper (Liu et al, 2017), Kobov experiments (Kabov, Scheid, Sharina, & Legros, 2002), and Kallidasis et al (2012) have all shown that as Bi and Bi w are less than 1, their effects on the Marangoni effect for film flow instability is small. Due to poor heat transfer characteristics at the liquid-gas interface and solid-gas interface, the actual Bi and Bi w values are very small.…”
Section: Linear Stability Analysismentioning
confidence: 92%
“…They discovered that a rivulet pattern is formed and aligned with the mean flow at small Reynolds numbers. The RWRM method, based on a weighted residuals model, is applicable for small to moderate Reynolds numbers (Liu, Jiang, & Duan, 2017;Ruyer-Quil et al, 2005). Compared with other methods, the RWRM model is simpler than the three-dimensional integration method of the conservation equations and is more accurate than either the BE or lubrication approximation models at moderate Reynolds numbers (Kalliadasis, Ruyer-Quil, Scheid, & Velarde, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…F x denotes an additional acceleration term. The drag force per unit droplet mass, namely, F D ( v − v p ), where F D can be written as follows: FD=3italicμCDRep4ρPDPitalic2 The dimensionless relative Reynolds number [ 22 ] (Re p ) is used to characterize the fluid flow and it can be expressed as follows [ 23 ] : Rep=italicρDpvtrue→vptrue→μ where D p is the particle diameter, and it follows Rosin–Rammler's distribution law.…”
Section: Methodsmentioning
confidence: 99%
“…The dimensionless relative Reynolds number [22] (Re p ) is used to characterize the fluid flow and it can be expressed as follows [23] :…”
Section: Governing Equationsmentioning
confidence: 99%